2012
DOI: 10.1242/jeb.073445
|View full text |Cite
|
Sign up to set email alerts
|

Annual cycles of metabolic rate are genetically determined but can be shifted by phenotypic flexibility

Abstract: SUMMARYBirds have adjusted their life history and physiological traits to the characteristics of the seasonally changing environments they inhabit. Annual cycles in physiology can result from phenotypic flexibility or from variation in its genetic basis. A key physiological trait that shows seasonal variation is basal metabolic rate (BMR). We studied genetic and phenotypic variation in the annual cycles of body mass, BMR and mass-specific BMR in three stonechat subspecies (Saxicola torquata) originating from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 63 publications
(102 reference statements)
2
13
0
Order By: Relevance
“…In contrast, when activation of breeding phenology is entirely plastic, populations in phenological asynchrony would have lower limitations to gene flow. Existing data are insufficient to determine whether differences in breeding timing between conspecific populations of birds generally reflects adaptive and genetic-based specialization or phenotypic plasticity (Nussey et al 2005;Charmantier and Gienapp 2014), although evidence exists for locally adapted cue-integration systems (Hahn and MacDougallShackleton 2008) and for high heritability in circannual rhythms (Hendry and Day 2005;Nussey et al 2005;Versteegh et al 2012). For instance, experiments involving translocation of individuals and monitoring of their breeding behavior have shown reduced fitness when individuals from populations breeding in asynchrony are grouped in the same place (Helm 2009; but see Martin et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, when activation of breeding phenology is entirely plastic, populations in phenological asynchrony would have lower limitations to gene flow. Existing data are insufficient to determine whether differences in breeding timing between conspecific populations of birds generally reflects adaptive and genetic-based specialization or phenotypic plasticity (Nussey et al 2005;Charmantier and Gienapp 2014), although evidence exists for locally adapted cue-integration systems (Hahn and MacDougallShackleton 2008) and for high heritability in circannual rhythms (Hendry and Day 2005;Nussey et al 2005;Versteegh et al 2012). For instance, experiments involving translocation of individuals and monitoring of their breeding behavior have shown reduced fitness when individuals from populations breeding in asynchrony are grouped in the same place (Helm 2009; but see Martin et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Inheritance of seasonal variation and seasonal traits (e.g. clutch size) has further been documented by crossbreeding and subsequent study of hybrids (Gwinner et al, 1995a;Helm, 2009;Tieleman et al, 2009;Versteegh et al, 2012a). If seasonal variation of constitutive immunity is driven more heavily by genetic components than environmental components, we would expect it to persist in captivity and to differ between subspecies.…”
Section: Introductionmentioning
confidence: 89%
“…Accordingly, organisms have adjusted their life histories and associated physiology to the variability of the environments they live in (Foster and Kreitzman, 2010;Klaassen, 1995;Nelson et al, 2002;Versteegh et al, 2012a). An important physiological system that relates to selfmaintenance and that connects life history traits with environmental factors is the immune system (Ricklefs and Wikelski, 2002;Sheldon and Verhulst, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common garden experiments in stonechats have also shown that tropical stonechats have lower CORT and resting metabolic rates than stonechats from the Northern hemisphere, and that this latter difference is heritable but sensitive to life-history stage [4, 49, 50, 88, 89]. One study investigated direct relationships between metabolic rates and CORT and found support for associations on the level of population, but not of individuals [50], thus overall supporting the idea of an involvement of CORT in differences of pace of life.…”
Section: Discussionmentioning
confidence: 99%